Appreciative inquiry: a promising research tool for rural tourism management - Che Aziz, Roslizawati; Abdul, Mohani; Abdul Aziz, Yuhanis; Abd Rahman, Azmawani (Cambridge Scholars Publishing, 2015)
Rural tourism has become an important developmental agenda and is consider a strong growing sector in the global tourism market. The protection and improvement of natural, built-environment, infrastructure and the economic growth, are the most significant contributions of this sector. The purpose and significance of developing rural tourism has become a major force in the rural economic development. Moreover, it has not only contributed towards poverty alleviation among the rural communities but has also generated a large-scale employment opportunities for the rural dwellers. Thus, with this in mind, the Appreciative Inquiry (AI) approach has been identified as an alternative tourism research tool for evaluating the contributions of rural tourism. The AI is one of the recent approaches used in tourism research.